Role of ginsenoside Rg1 as a PPAR-γ activator in protecting against manganese-induced hepatotoxicity: Insights into the TLR4/MyD88/MAPK signaling pathway - Mengjing Zhao; Min Zhang; Shoudong Ni (Ecotoxicology and Environmental Safety)
This study investigates the protective effect of ginsenoside Rg1 against manganese (Mn)-induced hepatotoxicity, highlighting its role as a PPAR-γ activator and its impact on TLR4/MyD88/MAPK pathway. Manganese induces liver damage through mechanisms involving oxidative stress and inflammation. Rg1, a principal bioactive compound of ginseng, significantly alleviates Mn-induced liver injury. Rg1 markedly enhances the activities of SOD, GSH, and CAT, while reducing levels of MDA and ROS, indicating an improvement in antioxidant defense capacity. Furthermore, Rg1 decreases inflammatory markers iNOS, TNF-α, IL-6, IL-12 and NO levels, underscoring its strong anti-inflammatory effects. Importantly, as a PPAR-γ activator, Rg1 upregulates PPAR-γ expression, subsequently inhibiting TLR4/MyD88/MAPK pathway. Additionally, silencing of PPAR-γ diminishes the protective effects of Rg1, while overexpression of PPAR-γ enhances them. The findings conclude that Rg1 exerts significant hepatoprotective effects against manganese-induced damage by activating PPAR-γ and modulating TLR4/MyD88/MAPK pathway, positioning it as a promising candidate for the treatment of Mn-induced hepatotoxicity.